Electrophysiological basis of cardiac arrhythmia in a mouse model of myotonic dystrophy type 1 - Ginjupalli, Vamsi Krishna Murthy; Cupelli, Michael; Reisqs, Jean-Baptiste; Sleiman, Yvonne; El-Sherif, Nabil; Gourdon, Genevieve; Puymirat, Jack; Chahine, Mohamed; Boutjdir, Mohamed (Frontiers in Physiology, 2023)
Introduction: Myotonic dystrophy type 1 (DM1) is a multisystemic genetic disorder caused by the increased number of CTG repeats in 3’UTR of Dystrophia Myotonia Protein Kinase (DMPK) gene. DM1 patients experience conduction abnormalities as well as atrial and ventricular arrhythmias with increased susceptibility to sudden cardiac death. The ionic basis of these electrical abnormalities is poorly understood. Methods: We evaluated the surface electrocardiogram (ECG) and key ion currents underlying the action potential (AP) in a mouse model of DM1, DMSXL which express over 1000 CTG repeats. Sodium current (INa), L-type calcium current (ICaL), transient outward potassium current (Ito) and APs were recorded using the patch-clamp technique. Results: Arrhythmic events on the ECG including sinus bradycardia, conduction defects, and premature ventricular and atrial arrhythmias were observed in DMSXL homozygous mice but not in WT mice. PR interval shortening was observed in homozygous mice while ECG parameters, QRS, and QTc intervals did not change. Further, flecainide prolonged PR, QRS and QTc visually in DMSXL homozygous mice. At the single ventricular myocyte level, we observed a reduced current density for Ito, and ICaL with a positive shift in steady state activation of L-type calcium channels carrying ICaL in DMSXL homozygous mice compared with WT mice. INa densities and action potential duration did not change between DMSXL and WT mice. Conclusion: The reduced current densities of Ito, ICaL and alterations in gating properties in L-type calcium channels may contribute to the ECG abnormalities in the DMSXL mouse model of DM1. These findings open new avenues for novel targeted therapeutics.